Homeopathic Perspective to Manage Pancreatic Disorders of Psychosomatic Origin (Homoeopathy for All, 2024)
An integrative approach combining conventional and alternative therapies like  homeopathy is essential for a holistic management of pancreatic disorders. This  approach acknowledges the complex etiology of these diseases and caters to  diverse patient needs, enhancing patient care through combined insights from  conventional medicine and holistic practices.
Keywords: Psychosomatic; Pancreatic